PENGARUH KOMPONEN ARUS KAS DAN LABA KOTOR TERHADAP RETURN SAHAM PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ 45 - admin, RICKY ALEXANDER B11112101 (Jurnal Manajemen Update, 2016)
Financial statements mayinclude cash flow statement and income statement, the charged components of cash flow information and gross profit, which is information that can be used by investors in investment decisions. This study aimed to determine the effect of changes in components of cash flow and gross profit to return stock companies listed in the LQ 45 index in the Indonesia Stock Exchange (BEI) by using signal theory. Samples in this study are 14 companies that located in LQ 45 respectively started from 2010 to 2014, were selected by using purposive sampling method. The data of this research is secondary data obtained from the financial statements of companies listed on the stock exchanges of Indonesia ( www.idx.co.id ). Technique of multiple regression analysis used is panel data. The dependent variable in this study is the stock return, while the independent variables are cash flows from operating, investing, financing, and gross profit. The results of this study are not all of independent variables have a significant effect on stock returns. Variable changes from operating activities have negative effect on stock returns and not significant, variable changes in cash flows of investment and no significant positive effect on stock returns, while the variable changes in cash flows financing activities and gross profit and significant positive effect on stock returns. Taken together the changes of components of cash flow and gross profit have a significant effect on stock returns. Keywords: Components of cash flow, gross profit, stock returns.